Insurance Costs - Manus O'Donnell (National Competitiveness and Productivity Council (NCPC), 2021)
Insurance markets are characterised by underwriting cycles - repeating, regular periods where insurance coverage is readily available at 'reasonable' prices (soft markets) and periods where prices are high, and coverage is limited or unavailable (hard markets). Available evidence suggests that liability insurance markets in Ireland are likely to have entered the 'hard market' phase as early as 2012. The Council believes that bringing award levels in line with other jurisdictions, ensuring consistency of award levels, and reducing settlement costs, are the key actions required to soften the Irish liability insurance market, and should lead to lower insurance costs and an increase the availability of insurance, and associated competitiveness. Key Actions in the Government's Action Plan for Insurance Reform, including the Personal Injuries Guidelines, should achieve this; if not - further actions, including Oireachtas Guidelines on award levels, need to be considered.
Keywords: 330